Mental Health and Wellness in Healthcare Workers Identifying Risks, Prevention, and Treatment. - Bowers, Clint A. (IGI Global, 2022)
Recent events have revealed that many healthcare workers are subject to very high levels of occupational stress, which has become particularly salient during the COVID-19 crisis. Recent research indicates that, due to a variety of occupational stressors, healthcare workers are at risk for a number of mental and physical ailments. Unfortunately, the literature on this topic is widely dispersed among numerous fields and must be accumulated to provide a thorough examination of the wellness of healthcare workers. Mental Health and Wellness in Healthcare Workers: Identifying Risks, Prevention, and.